A Multilayered Control of the Human Survival Motor Neuron Gene Expression by Alu Elements - Ottesen, Eric W.; Seo, Joonbae; Singh, Natalia N.; Singh, Ravindra N. (Frontiers in Microbiology, 2017)
Humans carry two nearly identical copies of Survival Motor Neuron gene: SMN1 and SMN2. Mutations or deletions of SMN1, which codes for SMN, cause spinal muscular atrophy (SMA), a leading genetic disease associated with infant mortality. Aberrant expression or localization of SMN has been also implicated in other pathological conditions, including male infertility, inclusion body myositis, amyotrophic lateral sclerosis and osteoarthritis. SMN2 fails to compensate for the loss of SMN1 due to skipping of exon 7, leading to the production of SMN7, an unstable protein. In addition, SMN7 is less functional due to the lack of a critical C-terminus of the full-length SMN, a multifunctional protein. Alu elements are specific to primates and are generally found within protein coding genes. About 41% of the human SMN gene including promoter region is occupied by more than 60 Alu-like sequences. Here we discuss how such an abundance of Alu-like sequences may contribute towards SMA pathogenesis. We describe the likely impact of Alu elements on expression of SMN. We have recently identified a novel exon 6B, created by exonization of an Alu-element located within SMN intron 6. Irrespective of the exon 7 inclusion or skipping, transcripts harboring exon 6B code for the same SMN6B protein that has altered C-terminus compared to the full-length SMN. We have demonstrated that SMN6B is more stable than SMNΔ7 and likely functions similarly to the full-length SMN. We discuss the possible mechanism(s) of regulation of SMN exon 6B splicing and potential consequences of the generation of the exon 6B-containing transcripts.